The Crime of All Crimes Toward a Criminology of Genocide - Rafter, Nicole (New York University Press, 2016)
Cambodia. Rwanda. Armenia. Nazi Germany. History remembers these places as the sites of unspeakable crimes against humanity, and indisputably, of genocide. Yet, throughout the twentieth century, the world has seen many instances of violence committed by states against certain groups within their borders—from the colonial ethnic cleansing the Germans committed against the Herero tribe in Africa, to the Katyn Forest Massacre, in which the Soviets shot over 20,000 Poles, to anti-communist mass murders in 1960s Indonesia. Are mass crimes against humanity like these still genocide? And how can an understanding of crime and criminals shed new light on how genocide—the "crime of all crimes"—transpires? In The Crime of All Crimes, criminologist Nicole Rafter takes an innovative approach to the study of genocide by comparing eight diverse genocides--large-scale and small; well-known and obscure—through the lens of criminal behavior. Rafter explores different models of genocidal activity, reflecting on the popular use of the Holocaust as a model for genocide and ways in which other genocides conform to different patterns. For instance, Rafter questions the assumption that only ethnic groups are targeted for genocidal "cleansing," and she also urges that actions such as genocidal rape be considered alongside traditional instances of genocidal violence. Further, by examining the causes of genocide on different levels, Rafter is able to construct profiles of typical victims and perpetrators and discuss means of preventing genocide, in addition to delving into the social psychology of genocidal behavior and the ways in which genocides are brought to an end. A sweeping and innovative investigation into the most tragic of events in the modern world, The Crime of All Crimes will fundamentally change how we think about genocide in the present day